Composite of titanium dioxide nanotube and cobalt sulfide for photoelectrochemical application - Mustafid Amna Rambey,; Siti Nurul Falaein Moridon,; Khuzaimah Arifin,; Lorna Jeffery Minggu,; Mohammad Kassim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
TiO2 nanotubes (NT) offer several advantages over other geometries for photoelectrochemical (PEC) applications. However, their performance in PEC water-splitting application has remained unsatisfactory due to its wide bandgap. To address this limitation, one approach is the incorporation of other materials as co-catalysts. Hence, in this study, a composite of TiO2 NT and cobalt sulfide (Cox Sy ) was successfully synthesized, and its potential as a photoelectrode for water molecules splitting was evaluated. The TiO2 NT was synthesized using electrochemical anodization of Ti foil, followed by annealing at 500 °C. Subsequently, Cox Sy was added to the TiO2 NT using hydrothermal method, and the composite was further annealed at 400 °C. Characterization technique, such as FESEM and XRD were employed to identify the morphological and phase structures, while UV-Vis reflectance spectroscopy was used for optical analysis. The efficiency of Cox Sy deposited on to TiO2 NT were evaluated by measuring the photocurrent generation. Remarkably, the sample of 60_Cox Sy /TiO2 NT exhibited photocurrent as high as 0.375 mA/ cm2 which is over sixfold higher than the bare TiO2 NT. The results reported in this study were higher than those reported previously.